PENGARUH KINERJA KEUANGAN TERDAHAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011 – 2013 - Nur Rachma (AkMen JURNAL ILMIAH, 2016)
This study aims to determine the effect current Ratio, Debt to Equity Ratio, Return on Equity, and Working Capital Turnover partially, or simultaneously to the stock price in Food and Beverage listed in the Indonesia Stosk Exchange year 2011 to 2013. The population in this study is of manufacturing subsector food and beverages listed oh the Indonesian stock exchange by 15 companies. Samples were ten (10) companies were selected based on criteria, namely : Food and Beverage Company listed on the Indonesia Stock Exchange years 2011 to 2013; Publish Audited financial statements; Has the advantage (profit) and never share cash dividend during the observation period. These results indicate that the Curent Ratio (X1) Debt to Equity Ratio (X2) and Working Capital Tornover (X4) partially no significant effect. While Return on Equity (X3) positive and significant impact on stock prices in food and beverage listed in the Indonesia Stock Exchange Year 2011 to 2013. Simultaneously Current Ratio (X1), Debt to Equity Ratio (X2), Return on Equity (X3), and the Working Capital Turnover (X4) Positive and significant effect on stock price in food and Beverage listed in the Indonesia Stock Exchange in 2011 to 2013. The dominant influential variable is Return on Equity (X3.